Growth Patterns, Body Weight, and Morphometric of KUB Chicken, Sentul Chicken and Arab Chicken - Depison Depison; Nabilah Ika Puteri; Gushairiyanto Gushairiyanto (Faculty of Animal Science, Universitas Gadjah Mada, 2020)
The purpose of this research was to determine the body weight, weight gain and morphometric characteristics of several local chicken strains. The research materials were KUB chicken, Sentul chicken, and Arab chicken. The method used was an experiment with a sample of 82 chickens from each strain. Data collected include body weight, weight gain, beak length, beak width, head length, head circumference, head height, neck length, neck circumference, wing length, back length, back height, chest length, chest width, shank length, shank circumference, tibia length, tibia circumference, third finger length, and pubic bone distance. Data collected were analyzed using the average difference test (t-test). The average value vector of body measurements of chicken lines was analyzed using the T²-Hotelling statistical test. Main Component Analysis statistical test was used to identify the shape and size characteristics of each chicken strain. The results showed that the body weight and morphometrics of KUB chickens at 3 months were significantly different (P<0.05) with Sentul chickens and Arab chickens. KUB chicken`s body weight gain at 3 months was not significantly different (P>0.05) from Sentul chickens, but it was significantly different (P<0.05) from Arab chickens. Body weight, weight gain, and morphometrics of KUB chickens were higher than Sentul chickens and Arab chickens. The size indicator in KUB chickens was the tibia length while in Sentul chickens and Arab chickens was chest length. The characteristic of KUB chickens was the back length, Sentul chickens was tibia length, and Arab chickens was the shank circumference.